2013
DOI: 10.1038/ncomms2936
|View full text |Cite
|
Sign up to set email alerts
|

Millisecond charge-parity fluctuations and induced decoherence in a superconducting transmon qubit

Abstract: The tunnelling of quasiparticles across Josephson junctions in superconducting quantum circuits is an intrinsic decoherence mechanism for qubit degrees of freedom. Understanding the limits imposed by quasiparticle tunnelling on qubit relaxation and dephasing is of theoretical and experimental interest, particularly as improved understanding of extrinsic mechanisms has allowed crossing the 100 microsecond mark in transmon-type charge qubits. Here, by integrating recent developments in high-fidelity qubit readou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
277
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(299 citation statements)
references
References 34 publications
18
277
4
Order By: Relevance
“…7a. The observed decay of the excited qubit state is described by an exponential relaxation, giving T 1 = 4.72 ± 0.06 μs, which compares favourably with the transmon relaxation times measured in earlier experiments [27,[29][30][31], but which is a factor of 30 below the state of the art [32][33][34].…”
Section: T 1 and T 2 Measurementssupporting
confidence: 85%
See 1 more Smart Citation
“…7a. The observed decay of the excited qubit state is described by an exponential relaxation, giving T 1 = 4.72 ± 0.06 μs, which compares favourably with the transmon relaxation times measured in earlier experiments [27,[29][30][31], but which is a factor of 30 below the state of the art [32][33][34].…”
Section: T 1 and T 2 Measurementssupporting
confidence: 85%
“…7bii) reveals two oscillating components of equal magnitude, separated in frequency by 554 kHz. We interpret these two components as arising from quasiparticle tunnelling events that take place on a characteristic timescale slow compared to each shot of the experiment, but fast compared to the 10 4 −10 5 realisations that are averaged to provide the detected signal [32]. The visible beating in our device is due to our choice of a relatively large E C in comparison with other qubits in the literature.…”
Section: T 1 and T 2 Measurementsmentioning
confidence: 92%
“…In the following paragraph we show that this pattern is robust against additional residual interactions such as g 1 g 2 , g 1 g 4 and g 3 g 4 couplings or when several transverse modes exist in the wire. A sensitive experimental technique 49 that relies on the Ramsey measurement was used recently for temporally tracking minute changes in the spectrum of the transmon (of the order of %0.04 of the transition frequency). It was demonstrated that for a device that has similar parameters to the one discussed here the transition rate for non-equilibrium quasiparticles was slow enough (milliseconds regime) to allow temporal tracking of the spectral structure.…”
Section: Detectible Experimental Signaturesmentioning
confidence: 99%
“…Later on, as the fabrication techniques progressed, it became possible to bring N S close to unity to reveal the parity effect of electrons on a superconducting island [10][11][12][13][14]. In recent years, the tunneling and relaxation dynamics of quasiparticles, which we address in this Letter, have become a topical subject because of their influence on practically all superconducting circuits in the low temperature limit [15][16][17][18][19][20][21][22].…”
mentioning
confidence: 95%